(untitled) (Texas Journal of Philology, Culture and History, 2025)
In pragma-linguistics, the category of the person is considered a pragmatic category encompassing a set of linguistic tools and communicative strategies through which attitudes towards a person are expressed: respect, contempt, submission, or the demonstration of authority; social distance is established and maintained; social or personal status is indicated; and specific communicative goals of participants in speech interaction are achieved. The category of the person is realized in texts through the use of addresses, honorific titles, designations of positions, epithets, metaphors, and lexical evaluation means. In other words, the category of the person is a system of linguistic and speech means by which a person, their place in society, and attitudes toward them are designated, characterized, and evaluated within a text or oral speech